Outpatient management of Gitelman's syndrome in pregnancy. (25th January 2013) - Mathen, Stephy; Venning, Michael; Gillham, Joanna
Abstract : Gitelman's syndrome is a congenital renal tubular defect which affects the apical membrane of the distal convoluted tubule of the renal system. The syndrome is characterised by hypokalaemia, hypomagnesaemia, metabolic alkalosis and hypocalcuria. There are only a few cases describing the impact of Gitelman's syndrome on pregnancy and the foetus. Although most pregnancies have favourable outcomes, fetal demise has been reported in the third trimester. We report the successful outcome of pregnancy in a patient with Gitelman's syndrome who continued on amiloride in pregnancy to optimise potassium and magnesium levels and review the literature for pregnancy outcomes of this condition.